United States government manual. - United States. Office of the Federal Register (Washington, D.C. Office of the Federal Register, 1973)
Annual
Published as a special edition of the Federal register.
Vols. for 1985/86- published by the Office of the Federal Register, National Archives and Records Administration.
Keywords: United States -- Executive departments -- Handbooks, manuals, etc; United States -- Politics and government -- Handbooks, manuals, etc